Condensation of 2D exciton-polaritons in an open-access microcavity - Li, F; Li, Y; Giriunas, L; Sich, M; Solnyshkov, DD; Malpuech, G; Trichet, AAP; Smith, JM; Clarke, E; Skolnick, MS; Krizhanovskii, DN (AIP Publishing, 2022)
We establish a tunable open-access microcavity consisting of two planar distributed Bragg reflectors (DBRs) individually controlled by nanopositioners. By varying the cavity length, such configuration enables variation of the light–matter coupling strength by a factor of 2, while keeping in microresonators the same active region and cavity mirrors. Polariton condensation was demonstrated over a large range of Rabi splittings and the corresponding threshold diagram was derived as a function of cavity-exciton detuning, which fits well with theoretical simulations. The results show that for various light-matter coupling strengths, optimal detunings featured by the lowest condensation threshold always occur at a fixed depth of energy trap between the exciton reservoir and the polariton ground state, which enables the most efficient exciton–exciton scattering into the condensate state in the driven-dissipative polaritonic system.